STUDY OF PROPER NAMES IN GERMAN FICTION (TAMADDUN NURI JURNALI, 2025)
In this article, after a few introductory words to important terms, various types of names, their functions and structures are considered. From the point of view of linguistics, artistic words occupy a special place in the studied area of ​​vocabulary, which play virtually no role in the word formation of the German language.